Binge-watching addiction on Over-the-Top (OTT) and its impact on academic performance among undergraduate students - Abdul Latiff, Dzaa Imma; Salleh @ Abdul Latif, Ahmad Syakir Salman; Megat Zambri, Wan Anis Aqilah; Kamal, Suhaila; Abu Bakar, Muhammad Nabihan (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The rise of video-on-demand in the streaming industry has contributed to binge-watching. Binge-watching can be defined as viewing two or more episodes of a series consecutively. The scenario of binge-watching has definite benefits and disadvantages for viewers. Binge-watching, due to its highly immersive nature, carries the risk of addiction, potentially resulting in a loss of control. Many studies have been conducted in discussion of mental health issues but less on students’ learning performance. This study surveyed 162 undergraduate students via purposive sampling using a 25-item instrument adapted from previous research on binge-watching addiction (BWA) and academic performance. The BWA Questionnaire, comprising 20 items across four domains which are Dependency, Avoidance, Craving, and Anticipation, were used along with academic performance items on a five-point Likert scale. Scores were categorized as low, moderate, and high levels of binge-watching. Data was analysed using multiple regression. The results show that Dependency (β=.00, p>0.05), Craving (β=.07, p>0.05), and Anticipation (β=.01, p>0.05) have insignificant relationships towards academic performance. This indicates that increased Dependency, Craving, and Anticipation of binge-watching do not lead to any significant changes in academic performance. However, Avoidance (β=.35, p<0.001) had a significant positive relationship, suggesting that students may downplay or hide their binge-watching habits, which in turn affects academic performance. Studies on binge-watching suggest that if done in moderation it is not dangerous. Thus, moderate behaviour on binge-watching is harmless and can be integrated into a balanced healthy lifestyle if students use it in a regulated manner without adversely affecting other sides of life.